2020
DOI: 10.1210/clinem/dgaa863
|View full text |Cite
|
Sign up to set email alerts
|

Dual GIP and GLP-1 Receptor Agonist Tirzepatide Improves Beta-cell Function and Insulin Sensitivity in Type 2 Diabetes

Abstract: Context Novel dual GIP and GLP-1 receptor agonist (RA) tirzepatide demonstrated substantially greater glucose control and weight loss (WL) compared with selective GLP-1RA dulaglutide. Objective Explore mechanisms of glucose control by tirzepatide. Design Post-hoc analyses of fasting biomarkers and multiple linear regression analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
153
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(167 citation statements)
references
References 47 publications
10
153
0
4
Order By: Relevance
“…Treatment with tirzepatide reduced both small LDLP and HDLP compared with dulaglutide, despite no differences being observed in either the LDL‐C or HDL‐C levels between the two treatments. These changes in lipoprotein subclass distribution may be secondary to improved insulin sensitivity with tirzepatide 34 . Taken together, the significant reductions in small LDLP, non‐HDL‐C and apoB levels, in addition to reductions of triglycerides and apoC‐III, point towards an overall less atherogenic lipoprotein profile in patients with T2D treated with tirzepatide.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment with tirzepatide reduced both small LDLP and HDLP compared with dulaglutide, despite no differences being observed in either the LDL‐C or HDL‐C levels between the two treatments. These changes in lipoprotein subclass distribution may be secondary to improved insulin sensitivity with tirzepatide 34 . Taken together, the significant reductions in small LDLP, non‐HDL‐C and apoB levels, in addition to reductions of triglycerides and apoC‐III, point towards an overall less atherogenic lipoprotein profile in patients with T2D treated with tirzepatide.…”
Section: Discussionmentioning
confidence: 96%
“…The clinical implications of these findings are that the weight-independent insulin sensitization identified here could offer greater treatment durability, in contrast to agents that provide only weight driven benefits. In support of this hypothesis, HOMA-IR analysis has suggested that a significant proportion of tirzepatide-induced insulin sensitization occurs in the absence of weight loss in subjects with T2DM (52). Together with studies showing that GIP can improve insulin sensitivity (23,24), this prompted the hypothesis that engagement of the GIPR may drive the weight-independent insulin sensitization action of tirzepatide.…”
Section: Discussionmentioning
confidence: 98%
“…Post hoc regression analysis of HOMA2-IR suggests that only 20-30% of the improvement in insulin sensitization by tirzepatide is due to weight loss [93], by contrast to GLP-1RAs where insulin sensitivity is attributed to weight loss only [94]. Additional studies with tirzepatide will more directly explore the effect of GIP/GLP-1 receptor agonism on pancreatic α cell function, β cell function, and whole-body insulin sensitivity (ClinicalTrials.gov identifier NCT03951753).…”
Section: Clinical Signs Of a Gip Benefitmentioning
confidence: 99%